Influence of Work Culture, Work Motivation and Job Satisfaction on Organizational Commitment - Kuswanto, Irfan -; Subiyanto, Didik -; Yulianto, Eko - (Admisi dan Bisnis, 2024)
This study aims to analyze the influence of work culture, work motivation, and job satisfaction on organizational commitment in employees of the Prambanan District Office. The specific objectives of this study are: 1) to analyze the influence of work culture on organizational commitment; 2) analyze the influence of work motivation on organizational commitment; 3) analyze the influence of job satisfaction on organizational commitment; and 4) analyze the simultaneous influence of work culture, work motivation, and job satisfaction on organizational commitment. The method used is a survey with the distribution of questionnaires as a primary data collection tool. This research was carried out in January 2024 at the Prambanan District Office, with a population of 50 employees, all of whom were respondents using the census method. Data was collected through a questionnaire based on the Likert scale, which measures positive and negative responses to research statements. Data analysis was carried out using Multiple Linear Regression. The results showed that work culture had a significant positive influence on organizational commitment, while work motivation and job satisfaction did not show a significant influence on organizational commitment. However, simultaneously, work culture, work motivation, and job satisfaction have a significant influence on organizational commitment. These findings provide insight into the factors that affect organizational commitment in the government office environment.